1991
DOI: 10.1002/aja.1001910107
|View full text |Cite
|
Sign up to set email alerts
|

Interodontoblastic collagen (von Korff fibers) and circumpulpal dentin formation: An Ultrathin serial section study in the cat

Abstract: The collagenous fibers of von Korff pass from the dentin matrix between the odontoblasts into the dental pulp. Although collagen fibrils are known to be present between odontoblasts, the existence of von Korff fibers has remained controversial. This may be because their continuity between the dentin matrix and the pulp has not been demonstrated ultrastructurally. In this study we have examined the odontoblast layer in the middle to apical regions of perfusion-fixed permanent canine teeth of cats by using trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The interodontoblastic spaces are very narrow, and the high density of intercellular junctions between odontoblasts make it difficult to identify the extracellular matrix in this layer. Scanning and transmission electron microscopical studies have revealed the presence of interodontoblastic collagen fibers, which cross the distal junctional complex of the odontoblasts and penetrate into and across the predentin (Bishop et al 1991;Salomon et al 1991;Tabata et al 1994). By using a confocal laser scanning microscope, we have observed the three-dimensional distribution of collagen type VI in the pulp of human teeth, especially in the odontoblast layer.…”
Section: Discussionmentioning
confidence: 95%
“…The interodontoblastic spaces are very narrow, and the high density of intercellular junctions between odontoblasts make it difficult to identify the extracellular matrix in this layer. Scanning and transmission electron microscopical studies have revealed the presence of interodontoblastic collagen fibers, which cross the distal junctional complex of the odontoblasts and penetrate into and across the predentin (Bishop et al 1991;Salomon et al 1991;Tabata et al 1994). By using a confocal laser scanning microscope, we have observed the three-dimensional distribution of collagen type VI in the pulp of human teeth, especially in the odontoblast layer.…”
Section: Discussionmentioning
confidence: 95%
“…1991). During secondary physiologic dentine formation, the pattern of interodontoblastic collagen fibre occurrence is irregular in cats (Bishop et al . 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recent transmission electron microscopy and scanning electron microscopic studies show the existence of interodontoblastic collagen fibres in human dentine (Sogaard‐Pedersen et al . 1990), in the root of cat dentine (Bishop et al . 1991) and in mechanically exposed monkey dental pulp (Kitasako et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent data from rat and cat molars suggest that the von Korff fibres originate in the pulp, pass through the odontoblast layer and the predentine and can be traced into the circumpulpal dentine of the crown (Bishop et al 1991) and the root (Salomon et al 1991).…”
Section: Introductionmentioning
confidence: 96%